MICROFINANCE INSTITUTIONS’ SUPPORT AND GROWTH OF SMALL AND MEDIUM ENTERPRISES - Abio Morris Geoffrey; Kalu Onwukwe Emenike (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2018)
This paper investigates the relationship between microfinance institutions’ (MFIs’) support and growth of small and medium size enterprises (SMEs) in Nimule, South Sudan. We use descriptive analysis, Pearson’s linear correlation coefficient (PLCC) analysis, and ordinary least square regression analysis to evaluate the responses obtained through questionnaires and interviews. The estimates of descriptive analysis show that majority of the respondents were females (53.7%); majority (33.7%) of the respondents had secondary education; and that the majority of respondents (46.3 %) have between 6-8 years experience. Results of the quantitative analysis using PLCC revealed that positive linear relationship exists between loan provision, savings account provision, managerial skills provision and growth of SMEs in Nimule, South Sudan. Similarly, results of the regression analysis indicate that loan provision, savings account provision, and managerial skills provision have positive and significant effect on SMEs growth in Nimule. These findings indicate, amongst others, that MFIs support contributes significantly to growth of SMEs in Nimule, South Sudan. The study recommends, among others, that MFIs should adopt Microfinance-group model as well as increase provision of non-financial services, such as managerial skills trainings, for SMEs.Keywords: microfinance institutions, SMEs growth, correlation, South Sudan.